Specific expression patterns of epithelial to mesenchymal transition factors in gestational molar disease. Issue 11 (November 2015) - Luchini, Claudio; Parcesepe, Pietro; Mafficini, Andrea; Nottegar, Alessia; Parolini, Claudia; Veronese, Nicola; Remo, Andrea; Manfrin, Erminia
Abstract: Introduction: The epithelial to mesenchymal transition, a well-known and re-emerging model in pathology, has not been completely investigated in the field of gestational pathology. This study aims at improving the comprehension of this process in molar disease, even looking for new possible immunohistochemical markers. Materials and methods: We have analysed the immunohistochemical expression of Twist1 and Snai2, two of the most important transcription factors involved in epithelial to mesenchymal transition, in formalin-fixed paraffin-embedded samples of 23 spontaneous abortive pregnancies, 22 molar pregnancies (10 partial and 12 complete) and 7 term placentas. Results: Twist1 and Snai2 were highly expressed in stromal villi cells of molar disease. Particularly, Twist1 was highly expressed in complete moles compared to both abortive pregnancies (p < 0.001) and partial moles (p < 0.05). Also Snai2 was more expressed by complete moles, differentiating them from non-molar abortions (p < 0.05). Discussion: On the basis of the known cadherins and claudins expression in these pathologies, our new findings reinforce the hypothesis of the involvement of epithelial to mesenchymal transition in early molar pregnancies and above all in complete moles. Furthermore, we highlighted that in molar disease not only the trophoblast, but even the villi stromal cells, are involved. Thanks to their specificity, furthermore, these Twist1 and Snai2 could be used as additional immunohistochemical tool in the diagnosis of complete molar disease, with Twist1 as the first choice. Highlights: Our aim is studying epithelial to mesenchymal transition markers in molar disease. We studied with whole-section immunohistochemistry the expression of Twist1 and Snai2. We conducted this study on abortive and molar tissues. Twist1 and Snai2 labelled with specific patterns stromal villi cells in molar disease. Twist1 could be useful in differential diagnosis between molar and non-molar abortions.